(untitled) (Horizontes de Enfermería, 2022)
The COVID-19 pandemic has become a global health problem, with Ecuador being one of the most affected Latin American countries. This disease has been classified as a trigger of stress in the population, causing prevention measures worldwide. The main objective of this study was to identify the causes that cause stress and anxiety in elementary school students in times of COVID-19 in the “Barrio Pupana Sur”. The research was quantitative, descriptive, cross-sectional, where a population sample of 200 primary school students was considered. Two surveys were used to collect the data, the childhood daily stress inventory test and the Spencer test. Similarly, the ethical principles indicated in the Declaration of Helsinki about research on human beings were taken into account, taking into account the ethical principles of respect, confidentiality and autonomy of the study participants. The results obtained showed a low level of stress and anxiety, in the different categories, such as health problems 86.5%, school environment 81.5%, family environment 90%, panic attack and agoraphobia 96.1%, separation anxiety 96.5%, social phobia 91%, fear of physical harm 94.5%, obsessive-compulsive disorder 95%, generalized anxiety disorder 97.5%. Concluding that there are several reasons why the level of stress and anxiety is low, among them we have the constant help of parents, dynamic strategies by teachers, allowing an excellent academic performance.